Identification and Analysis of the Chloroplast rpoC1 Gene Differentially Expressed in Wild Ginseng - Lee Kwang-Ho; Kwon Ki-Rok; Kang Won-Mo; Jeon Eun-Mi; Jang Jun-Hyeog (Korean Pharmacopuncture Institute, 2012)
Panax ginseng is a well-known herbal medicine in traditional Asian medicine, and wild ginseng is widely accepted to be more active than cultivated ginseng in chemoprevention. However, little has actually been reported on the difference between wild ginseng and cultivated ginseng. Thus, to identify and analyze those differences, we used suppressive subtraction hybridization (SSH) sequences with microarrays, realtime polymerase chain reaction (PCR), and reverse transcription PCRs (RT-PCRs). One of the clones isolated in this research was the chloroplast rpoC1 gene, a β subunit of RNA polymerase. Real-time RT-PCR results showed that the expression of the rpoC1 gene was significantly upregulated in wild ginseng as compared to cultivated ginseng, so, we conclude that the rpoC1 gene may be one of the important markers of wild ginseng.